CELLULAR AUTOMATA SIMULATION OF THE DISTRIBUTION OF SHRINKAGE DEFECTS IN CASTING «BEARING HOUSINGS» WITH PROFITS AT DIFFERENT METAL LEADING - A. N. Chichko; S. G. Lihouzov; O. A. Sachek; Y. V. Jackiewicz; V. F. Sobolev; T. V. Matyushinets; O. I. Chichko (Литьë и металлургия)
Cellular automata simulation of the distribution of shrinkage defects in the casting of «The bearing housing» with a head during the metal flow to various parts of the casting was held. It is established that the casting is completely filled with metal, without forming runout, for the considered options for the metal flow. It is established that during the metal flow to the massive part, a bubbles up to 739 cm3 were formed, which is 69% less than in the same form without a head (2,355 cm3).